The first translations of Leatherstocking tales in Slovene - Darja Mazi-Leskovar (Acta Neophilologica, 2007)
The Leatherstocking Tales represent what is probably the most valuable contribution of James Fenimore Cooper to the development of American literature. This article surveys briefly the first translation of the series, by highlighting the domestication and the foreignization procedures which were applied to make the books accessible for the target audience. Secondly, it discusses the interplay of domestication and foreignization with regard to the forms and functions of proper names.